2021
DOI: 10.1097/cm9.0000000000001683
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analysis vs. karyotyping for fetal ventriculomegaly: a meta-analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…When VM is identified, a thorough evaluation should be performed, including detailed ultrasound assessment of the fetal anatomy, consideration of fetal MRI, amniocentesis for karyotype and chromosomal microarray (CMA), and investigations for fetal infection 2,5,6 . Chromosomal abnormalities have been reported in studies ranging from 2.7–7% 7,11,12 . The incidence of additional CNS and non‐CNS ultrasonographic abnormalities ranges from 10% to 76% but appears to be <50% in most studies 5,13–18 .…”
Section: Introductionmentioning
confidence: 99%
“…When VM is identified, a thorough evaluation should be performed, including detailed ultrasound assessment of the fetal anatomy, consideration of fetal MRI, amniocentesis for karyotype and chromosomal microarray (CMA), and investigations for fetal infection 2,5,6 . Chromosomal abnormalities have been reported in studies ranging from 2.7–7% 7,11,12 . The incidence of additional CNS and non‐CNS ultrasonographic abnormalities ranges from 10% to 76% but appears to be <50% in most studies 5,13–18 .…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort study, the overall detection rate of chromosomal abnormality in VM was 9.1% for karyotyping. A previous meta-analysis involving the genetic etiology of VM indicated that the incidence rate of chromosomal abnormalities in fetal VM was ranging from 0 to 25% ( 1 ). In recent years, a number of studies have further enriched the incidence rates of chromosomal abnormalities in VM by karyotyping.…”
Section: Discussionmentioning
confidence: 99%
“…For our VM cases, the detection rate of chromosomal abnormality using CMA was 16.5%, slightly lower than some studies reporting 17.9–20.6% ( 2 , 17 ) and higher than other studies reporting 6.2–16.3% ( 3 , 10 , 11 , 18 – 20 ). It has been reported that CMA could yield an additional detection rate as a first-tier diagnostic tool in VM, with an incremental yield ranging from 5 to 26% ( 1 , 8 ). Some recent studies with larger sample sizes have also described that CMA could provide an additional diagnosis rate of 4.4–10.6% in VM ( 2 , 10 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations